Comparative toxicity of urban wastewater and rainfall overflow in caged freshwater mussel Elliptio complanata - André, C.; Duy, S. V.; Sauvé, S.; Gagné, F. (Frontiers in Physiology, 2023)
Municipal effluents are well recognized to disrupt sexual differentiation and reproduction in mussels. However, the contribution of rainfall combined with sewer overflows (increased by rain from climate changes) to this problem is not well understood. The purpose of this study was to compare the neuroendocrine effects of municipal discharges and rainfall overflows in caged endemic mussels Elliptio complanata. To examine this, mussels were experimentally caged and placed for 3 months at a municipal effluent dispersion plume and overflow sites. The data revealed that downstream surface waters contained some pharmaceuticals (caffeine, carbamazepine) and accumulated important levels of heterotrophic bacteria but not at the overflow sites. The principal effects observed at the downstream site were increased soft tissue mass (and gonad index), inflammation and Vtg protein in male mussels as determined by a novel immunostaining methodology. The rainfall overflow sites had no effects on these responses but specifically reduced Vtg proteins in females, dopamine (Dop), gonad lipids, DNA strand breaks with increased metallothioneins. In conclusion, the observed feminization effects of the municipal effluent were not observed in mussels caged at rainfall overflow sites although they showed a different pattern of toxicity.